Study of Phenotypes Variability of Pollen Grains Malus domestica Borkh. by Scanning Electron Microscopy - Horčinová Sedláčková, Vladimíra; Hulin, Miloš; Ostrovský, Radovan; Motyleva, Svetlana (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2021)
The studying of Malus domestica Borkh. pollen allows us to determine the details of morphological characteristics and describe the most important parameters and pollen sculpture that can be used to identify representatives of species. We analysed pollen morphology of seven Malus domestica genotypes from old and local varieties from the territory of Slovakia via a scanning electron microscope. We used principal components analysis to explore variability in pollen grain size (polar and equatorial diameter), shape, aperture type, and exine ornamentation. The complexity of these morphological characteristics and ultrastructure allows determining the differences or similarities between the same and various species and genotypes, which may be a useful tool for systematics with significant diagnostic value. Findings confirmed small differences among the genotypes in measured traits with polar and equatorial diameters in the range from 31.85 to 42.85 μm and from 21.23 to 23.93 μm, respectively. Shape index (P/E ratio) depending on elongation or roundness of pollen grains varied from 1.44 to 1.87. Hierarchical cluster analysis and principal component analysis of morphological data helped to compare evaluated morphometric parameters and identified five closely related groups. It was noted that diversity of surface sculpturing of pollen grains in combination with shape and size enables to use of a complex of thin morphologic signs for M. domestica pollen identifications. Pollen data combined with other morphological evidence (e.g., floral characters) have more recently become an important indicator of which genotypes may be the best representatives of species.